Integrating Local Wisdom and Socio-Scientific Issues: The Impact of the Ethno-SSI Module on Students' Problem-Solving Skills - I Nyoman Selamat; Luh Mitha Priyanka (Universitas Pendidikan Ganesha, 2024)
Problem-solving skills in science learning remain low due to ineffective instructional methods, necessitating innovative designs such as the ethno-SSI module, which integrates local wisdom and socioscientific issues to enhance students' motivation and higher-order thinking skills. This study aims to analyze the differences in problem-solving skills between classes using the ethno-SSI module and those employing conventional teaching materials. This research adopts an experimental approach with a pretest-posttest control group design. The developed ethno-SSI module is implemented in the experimental class, while the control class utilizes conventional instructional materials. At the end of the learning process, students' problem-solving skills are assessed using a problem-solving test. The findings reveal a significant difference between the two groups, with the experimental class achieving an average problem-solving skill score of 70, compared to only 50 in the control class. The use of the ethno-SSI module in science learning has proven to be more effective in enhancing students' problem-solving skills than conventional teaching materials, as evidenced by the significant difference in scores between the two groups.